Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 202328 by MATHEMATICSAM last updated on 24/Dec/23

If n ≥ 2 and U_n  = (3 + (√5))^n  + (3 − (√5))^n   then prove that U_(n + 1)  = 6U_n  − 4U_(n − 1)  .

Ifn2andUn=(3+5)n+(35)nthenprovethatUn+1=6Un4Un1.

Commented by aleks041103 last updated on 24/Dec/23

It is true even for n=1

Itistrueevenforn=1

Answered by aleks041103 last updated on 24/Dec/23

U_(n+1) +4U_(n−1) −6U_n =  =(3+(√5))^(n−1) ((3+(√5))^2 +4−6(3+(√5)))+  (3−(√5))^(n−1) ((3−(√5))^2 +4−6(3−(√5)))  (3+(√5))^2 =14+6(√5)  ⇒(14+6(√5))+4−18−6(√5)=0  (3−(√5))^2 =14−6(√5)  (14−6(√5))+4−18+6(√5)=0  ⇒U_(n+1) −6U_n +4U_(n−1) =  =(3+(√5))^(n−1) (0)+(3−(√5))^(n−1) (0)=0    ⇒U_(n+1) =6U_n −4U_(n−1)

Un+1+4Un16Un==(3+5)n1((3+5)2+46(3+5))+(35)n1((35)2+46(35))(3+5)2=14+65(14+65)+41865=0(35)2=1465(1465)+418+65=0Un+16Un+4Un1==(3+5)n1(0)+(35)n1(0)=0Un+1=6Un4Un1

Terms of Service

Privacy Policy

Contact: info@tinkutara.com